Crowdsourcing evolution: Towards a taxonomy of crowdsourcing initiatives - Aris H.; Din M.M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Taxonomies; Ubiquitous computing; Systematic Review; Crowdsourcing